Marcado diferencial de objeto y semántica verbal en español - Heredero, Diego Romero (Beihefte zur Zeitschrift für romanische Philologie, 2022)
The book examines the impact of verbal semantics - telicity and affectedness, mostly - on differential object marking (DOM) in Spanish. It presents two studies providing empirical evidence for earlier claims and, additionally, integrates the results into an explanatory model based on the concept of prominence.